Botulinum Toxin for Painful Spasms From Focal Seizures: Theoretical Considerations and Case Report. Issue 1 (January 2013) - Wilkenfeld, Ari J.L.; Frank, Samuel A.; McCarthy, David C.
Abstract : Introduction: Botulinum toxin (BTX) has been used to treat muscle overactivity and can reduce pain from muscle spasm. There are no previous reports to our knowledge of using BTX to treat the pain from intractable focal motor seizures. Case Report: We present a case of chronic, focal, muscle pain, and spasm secondary to intractable focal motor seizures treated with BTX. The patient experienced significant relief in muscle pain despite continued seizures. Conclusions: On the basis of the case presented, BTX may have a limited role in the treatment of pain from muscle spasm in intractable focal seizures. Further study is necessary to see if this use of BTX is generally applicable. Abstract : Supplemental Digital Content is available in the text.